2015
DOI: 10.1016/j.bios.2014.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Engineering plasmonic nanorod arrays for colon cancer marker detection

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Dodson et al developed a periodic Au nanorod array for the detection of single nucleotide polymorphisms (SNP) in a gene that is frequently occurring in early stages of colon cancer with an LOD under 10 nm [63]. However, the study shows preliminary results, as it did not include any type of microfluidic cell, it involves static measurements, and no real samples (or spiked complex samples) have been assessed so far.…”
Section: Bioanalytical and Clinical Applicationsmentioning
confidence: 99%
“…Dodson et al developed a periodic Au nanorod array for the detection of single nucleotide polymorphisms (SNP) in a gene that is frequently occurring in early stages of colon cancer with an LOD under 10 nm [63]. However, the study shows preliminary results, as it did not include any type of microfluidic cell, it involves static measurements, and no real samples (or spiked complex samples) have been assessed so far.…”
Section: Bioanalytical and Clinical Applicationsmentioning
confidence: 99%
“…88 As an emerging future technology, nanoantennas can be used for early detection of cancerous tumours 243,244 which will lead to the development of effective cancer treatment. Few recent works have shown that biosensing based on surface plasmon resonance (SPR) has proved to be effective in label-free tumor detection [245][246][247][248] and can be used to detect a single molecule of an early stage tumor. Currently, research and development are in progress in making a nanoantenna based SPR biosensor which will be able to detect cancer cells at an early stage.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Various types of planar resonators, including split ring resonators (SRR), nanorods, crescents, and pyramids have been reported to have sensitivities of 100–300 nm per RIU and FOM of ≈2 in the visible frequency range. Higher sensitivity is achievable in self‐assembled metal nanoparticles due to their lower damping loss and negligible interaction with the substrate .…”
Section: Introductionmentioning
confidence: 99%